A new structural model of the Pachitea Basin, Peru: Interaction of thick-skinned tectonics and salt detached thrusting. (November 2015) - Witte, J.; Rebaza, J.; Westlund, D.; Stratton, M.; Alegria, C.
Abstract: We present four new structural transects, a new seismo–stratigraphic correlation, a refined structural model and new shortening rates for the Pachitea Basin (=PB), Peru. Our results are based on the integration and detailed interpretation of newly acquired industry seismic (2D, 2005 vintage), existing well data, existing and proprietary surface geology data and newly acquired aero magnetic data (2007 vintage). Our assessment confirms the presence of at least four distinct structural styles in the area, thick-skinned structures, thin-skinned detachment thrusting, salt-tectonics and localized strike-slip tectonics. Based on seismo–stratigraphic correlations we conclude that the oldest rocks carried to outcrop by the San Matias (=SM) thrust are of Jurassic age. We interpret the thin-skinned master detachment to be located in varying positions, directly below or above, autochtonous salt pillows. Timing assessment of the SM thrust sheet reveals that it has been active from at least ∼5 Ma to post-2 Ma, supporting regionally published timing data for this latitude. Positive topographic surface expressions indicate ongoing contraction along the mountain front of the Peruvian Eastern Cordillera (=EC). Across the PB we calculate between 2.6% and 5.5% for thick-skinned shortening and at least 25.5% for the thin-skinned shortening. For the SM thrust sheet we calculate a slip-rate of ∼1–1.6 mm/yr, which is in line with published slip rates on individual thrusts from around the world. Observations along the SM thrust system indicate that thin- and thick-skinned systems interact mechanically, and that they have been active intermittently. We conclude that the location of salt pillows as well as pre-existing or growing basement-involved structures helped trigger the SM thrust. Different types of salt bodies are present in the PB, autochtonous pillows, slightly thrusted pillows and allochtonous diapirs. Our results provide new insight into the structural interplay, particularly how thick-, thin-skinned and salt tectonics interacted to form the present-day structural configuration. The interplay of the distinct structural styles has direct control on the trapping styles of hydrocarbons in the area. Trapping potential for hydrocarbons in the PB is related to thick-skinned (basement-involved) structures, located in the SM footwall, as well as classic thin-skinned thrusting (salt or shale detached) and possibly to wrench-related structures. In order to unlock the exploration potential of this area additional seismic, outcrop work and geochemical data are necessary. Future research should focus on apatite fission track analysis and GPS stations on some of the key basement-cored structures.